Hubungan Faktor Jenis Kelamin, Pekerjaan dan Pengalaman Menjalani Operasi terhadap Kecemasan pada Pasien Pre Operasi Fraktur Ekstremitas Bawah di Instalasi Bedah Sentral RSUD Mardi Waluyo Blitar - Adi Saputra, Okta; Taufan; Sepdianto , Tri Cahyo; Marsaid (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Objective: The general objective of this study was to determine the factors that influence anxiety in preoperative lower extremity fracture patients at the IBS RSUD Mardi Waluyo Blitar. The specific objectives of this study were 1. to analyze gender factors on anxiety in preoperative lower extremity fracture patients at the IBS RSUD Mardi Waluyo Blitar, 2. to analyze occupational factors on anxiety in preoperative lower extremity fracture patients at the IBS RSUD Mardi Waluyo Blitar, 3. to analyze factors of surgical experience on anxiety in preoperative lower extremity fracture patients at the IBS RSUD Mardi Waluyo Blitar. Methods: : Cross-sectional research design, research population 30 lower extremity fracture patients, independent variables (gender, occupation, experience of undergoing surgery) and dependent variables (anxiety), Observation research instruments and APAIS questionnaires, research location premedication room central surgical installation RSUD Mardi Waluyo Blitar, research time 26 March - 19 April 2025, research data processing editing coding, data entry and cleaning, data analysis statistical test SPSS using chi square test and descriptive analysis. Results: 1. The significance value (Sig. 2-tailed) is 0.003, which is smaller than α = 0.05 (p < 0.05). This shows that there is a significant relationship between variable X (gender factor) and variable Y (anxiety level). 2. The significance value (Sig. 2-tailed) is 0.006 which is smaller than α = 0.05 (p < 0.05). This shows that there is a significant relationship between variable X (job factor) and variable Y (anxiety level). 3. The significance value (Sig. 2-tailed) is 0.008 which is smaller than α = 0.05 (p < 0.05). This shows that there is a significant relationship between variable X (operation experience factor) and variable Y (anxiety level). Conclusion: 1. The gender factor is related to anxiety with a p value of 0.004, < of (p < 0.05). 2. There is a relationship between work factors and anxiety with a p value of 0.006, < of (p < 0.05). 3. The experience of undergoing surgery has a relationship with anxiety with a p value of 0.008, < of (p < 0.05).